Prosedur Pemeriksaan MRI Brain Pada Kasus Stroke Hemoragik - Prita Prita; I Made Lana Prasetya; Rahmat Widodo (Pusat riset dan Inovasi Nasional, 2023)
Magnetic Resonance Imaging (MRI) is a medical imaging technique that combines magnetic fields and radio waves to create images and analysis of body tissue, blood circulation and metabolic function of the body. Some indications for MRI brain include detecting and identifying cases such as multiple sclerosis, infarction, hemorrhage, infection, trauma, and tumor or metastatic disease. Hemorrhagic stroke is bleeding that occurs when the blood vessels leading to the brain leak. Hemorrhagic stroke occurs when blood comes out of a blood vessel due to tearing of the blood vessel wall. Blood vessel walls can be weakened by the process of atherosclerosis and can also be due to congenital defects. The research method used was qualitative research. With a case study type of research. Data collection was carried out from July 2023 to August 2023 using a 3 Tesla MRI aircraft. The patient samples used in this study were three patients with complaints in the head. Data collection was carried out through observation, interviews and documentation. The MRI brain examination procedure in hemorrhagic stroke cases at one of the hospitals in Jakarta uses the Plain localizer axial, sagittal and coronal sequence, T1_fl2_axial, T2_tse_darkfluid_axial, T2_tse_axial, ep2d_diff_4scan_trace, asl_3d_axial, tof_cs_carotids, flow_pc3d_MRV, tof_brain_MRA, T2_swi_axial. In this case, there is a different sequence used, namely T2_swi_axial. Sequence susceptibility weighted imaging (SWI) is an innovative radiological imaging method that is often used in diagnosing neuroradiological disorders.